Morphometric Analysis of the Human Second Cervical Vertebrae of North Indian Population - Seema Tabassum; N. B. Singh; S. K. Karn (Academia Anatomica International, 2019)
Introduction: The Aim of the study was to provide the morphometric measurement of the axis vertebrae in North Indian popuulation. Which could be used as clinical tool to determine the feasibility of safe translaminar screw placement. Subjects and Methods: 50 dry human axis vertebrae from adult North Indian population were subjected to morphometric measurement using venier caliper. The various dimensions of the axis vertebrae were observed. Results: There is high variability in the thickness of the C2 lamina. As compared to western population, the axis bones used in the present study had smaller profiles. Conclusion: The current study showed safety margin for translaminar screw insertion is low.